What Do We Have to Know about PD-L1 Expression in Prostate Cancer? A Systematic Literature Review. Part 5: Epigenetic Regulation of PD-L1 - Andrea Palicelli (MDPI AG, 2021)
Epigenetic alterations (including DNA methylation or miRNAs) influence oncogene/oncosuppressor gene expression without changing the DNA sequence. Prostate cancer (PC) displays a complex genetic and epigenetic regulation of cell-growth pathways and tumor progression. We performed a systematic literature review (following PRISMA guidelines) focused on the epigenetic regulation of PD-L1 expression in PC. In PC cell lines, CpG island methylation of the CD274 promoter negatively regulated PD-L1 expression. Histone modifiers also influence the PD-L1 transcription rate: the deletion or silencing of the histone modifiers MLL3/MML1 can positively regulate PD-L1 expression. Epigenetic drugs (EDs) may be promising in reprogramming tumor cells, reversing epigenetic modifications, and cancer immune evasion. EDs promoting a chromatin-inactive transcriptional state (such as bromodomain or p300/CBP inhibitors) downregulated PD-L1, while EDs favoring a chromatin-active state (i.e., histone deacetylase inhibitors) increased PD-L1 expression. miRNAs can regulate PD-L1 at a post-transcriptional level. miR-195/miR-16 were negatively associated with PD-L1 expression and positively correlated to longer biochemical recurrence-free survival; they also enhanced the radiotherapy efficacy in PC cell lines. miR-197 and miR-200a-c positively correlated to PD-L1 mRNA levels and inversely correlated to the methylation of PD-L1 promoter in a large series. miR-570, miR-34a and miR-513 may also be involved in epigenetic regulation.